2018
DOI: 10.1080/16549716.2018.1496972
|View full text |Cite
|
Sign up to set email alerts
|

Subnational regional inequality in access to improved drinking water and sanitation in Indonesia: results from the 2015 Indonesian National Socioeconomic Survey (SUSENAS)

Abstract: Background: Universal and equitable access to safe and affordable drinking water and adequate sanitation and hygiene in Indonesia are vital to ensure healthy lives and promote well-being for all at all ages. Objectives: To quantify subnational regional inequality in access to improved drinking water and sanitation in Indonesia. Methods: Data about access to improved drinking water and sanitation were derived from the 2015 Indonesian National Socioeconomic Survey (SUSENAS) and disaggregated by 510 districts acr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 10 publications
(10 reference statements)
1
33
1
1
Order By: Relevance
“…Inter-provincial and center-periphery inequalities in drinking water sources and services illustrate that besides urban and rural setting, populations in different geographical zones (e.g. center and periphery) within the country are potentially at different 'risk' when it comes to water (under)supply (Adams and Smiley 2018, Afifah et al 2018, Pullan et al 2014, Smith 2008, Yu et al 2014.…”
Section: Geographic Location and Centrality And Provincial Inequalitiesmentioning
confidence: 99%
“…Inter-provincial and center-periphery inequalities in drinking water sources and services illustrate that besides urban and rural setting, populations in different geographical zones (e.g. center and periphery) within the country are potentially at different 'risk' when it comes to water (under)supply (Adams and Smiley 2018, Afifah et al 2018, Pullan et al 2014, Smith 2008, Yu et al 2014.…”
Section: Geographic Location and Centrality And Provincial Inequalitiesmentioning
confidence: 99%
“…mean difference from mean and weighted index of disparity) [6]. Large variation in inequality was observed within provinces with the same numbers of districts.…”
mentioning
confidence: 99%
“…Data from different national sources, including health facility surveys and household surveys, were used to assess inequalities in selected indicators by relevant dimensions of inequality. For example, data from the 2015 National Socioeconomic Survey (SUSENAS) were used to assess inequalities in access to improved drinking water between districts [17]. Overall, it was found that there were large variations between districts within each province (see Figure 4).…”
Section: Usementioning
confidence: 99%
“…Moreover, feedback from users helped to improve the template as well as the warning messages that appear in HEAT Plus if data have not been entered correctly. The results from the capacity building process have been presented in the national report State of health inequality : Indonesia , published in November 2017, as well as in this special issue [17,18]. …”
Section: Usementioning
confidence: 99%